STRATEGIES TO BECOME A HAFIDZ AND HAFIDZAH WITH MATHEMATICAL MODELING - Mohammad Tohir; Moh. Mu’afi (LP2M Universitas Ibrahimy, 2022)
Based on the reasoning of the Qur'an and Hadith, the practice of memorizing the Qur'an was a specific devotion and the Sunnah of the Prophet that was highly noble and had exceptional value for people who carry it out. The goal of this research was to examine the approach of memorizing the Qur'an in a specific amount of time based on mathematical modelling. The Salafiyah Syafi'iyah Islamic Boarding School Sukorejo, Sitobondo, Indonesia, was used for this study. The research approach utilized in this discussion to remember 30 juz of the Qur'an was the Research and Development method. The study's findings show that: (1) there were several methods of memorizing the Qur'an, such as kaisa, tasalsuli, jam'ii, muqsam, and so on; (2) there were patterns of deposit in memorizing the Qur'an every week, namely 2/5 juz per week or 6/5 juz per month; and (3) there was a mathematical formula for memorizing the Qur'an, namely y = 0.3x with R.